A Comparative Study on the Joint Coordination of Archery Athletes of Different Skill Levels: Based on Functional Data Analysis - Zhang, Baifa; Lin, Zhi-Cheng (Quality in Sport, 2024)
Purpose: Joint coordination is a critical factor influencing high-quality technical movements. By analyzing the changes between joints through functional data analysis, characteristic parameters can be derived. This study employs functional data analysis to explore the differences in joint coordination characteristics among archery athletes at various skill levels, offering a new perspective for coaches and athletes to analyze specific movement techniques. Methods: Twenty-eight archery athletes were selected as subjects, including eight international master athletes, twelve national first-level athletes, and eight national second-level athletes from Chinese national and province team. An infrared light spot motion capture system was utilized to gather kinematic parameters during the archery shooting process. Functional data analysis was employed to determine the upper limb joint coordination characteristic parameters of athletes at different skill levels. Results: Archery athletes at different levels exhibit three types of joint coordination characteristics between the shoulder and elbow joints during the drawing and aiming phases. The first type of joint coordination characteristic shows statistical differences across levels (P=0.03). These differences are primarily due to the following: 1) For international master athletes, the movement speeds of the shoulder and elbow joints both peak in the early phase of drawing; 2) The range of coupled motion between the shoulder and elbow joints is higher in the early phase of drawing and lower in the latter half, and consistently lower during the aiming phase; 3) The duration of the drawing phase is shorter. Conclusion: Functional data analysis effectively captures the differences in upper limb joint coordination characteristics among archery athletes at various levels. Superior athletes typically exhibit synchronous shoulder-elbow joint movements, enhanced feedforward capabilities, and a quicker rhythm of movement.